A new species of large Hemiandrus ground wētā (Orthoptera: Anostostomatidae) from North Island, New Zealand - Trewick, Steven A. (Zootaxa, 2021)
A new species of Hemiandrus ground wētā is described from North Island, New Zealand. Hemiandrus jacinda sp. nov. is larger and more brightly coloured than other species in the region, but appears to be scarce and restricted to remnant native forest habitat.